Promoting cooperative behavior for people with disabilities: focus on the fact that “anyone may become a person with disabilities” - Yuho Shimizu (Frontiers in Social Psychology, 2025)
Around the world, forming societies in which people with disabilities (PWD) can play an active role alongside able-bodied people (AP) is expected. However, prejudice against PWD held by AP persists. Therefore, reducing prejudice against PWD and promoting cooperative behavior for PWD are important. Meanwhile, PWD are characterized by the fact that “anyone may become a person with disabilities.” Considering this viewpoint, we tested the hypotheses that presenting participants with an explanatory statement emphasizing that anyone may become a person with disabilities will reduce prejudice against PWD (Hypothesis 1) and increase cooperative behavior for PWD (Hypothesis 2). An online experiment was conducted and data from 354 Japanese AP (22–69 years, 226 males and 128 females) were analyzed. Cooperative behavior was measured by a one-time public goods game. Results showed that presenting the above-mentioned statement did not reduce participants' prejudice against PWD (not supporting Hypothesis 1), but it increased cooperative behavior for PWD (supporting Hypothesis 2). In other words, participants in the experimental group were not willing to move closer psychologically toward PWD, but participants were willing to cooperate with PWD just in case participants were to become PWD. Effective strategies to reduce prejudice should continue to be explored.